An Account of Señorita Maquiladora - Rosina Conde (Studies in 20th & 21st Century Literature, 2008)
Performer and scholar Rosina Conde finds that Señorita Maquiladora is the performance piece that has gone through the most transformations, not in its script, but in its text, as it is constantly being rewritten to speak to contemporary social issues. She believes that Señorita Maquiladora has potential because it speaks to global themes that affect workers in the assembly plant industry, not only with respect to the questions of the environment and health, but also in terms of the patriarchial patterns that force these women to compete in an atmosphere of a vertical structure dominated by men, with all the attendant disadvantages, without taking into account that women are responsible for procreation. Feminicide, health problems like breast and uterine cancer, and the birth of anacephalic children are only a few conditions suffered by this group of women who remain today the most vulnerable sector of the Mexican workforce.
Keywords: Rosina Conde; Señorita Maquiladora; social issues; maquiladoras; environmental issues; patriarchy; women; feminicide; Mexican workforce; Mexican performance